Computer systems : a programmer's perspective - Bryant, Randal. 4 0 16; O'Hallaron, David Richard; 5 (Boston : Pearson, 2011)
Computer Systems: A Programmer's Perspective, Second Edition, introduces the important and enduring concepts that underlie computer systems by showing how these ideas affect the correctness, performance, and utility of application programs. Other systems books, written from a builder's perspective, describe how to implement the hardware or some portion of the system software, such as the operating system, compiler, or network interface. This book is written from a programmer's perspective, describing how application programmers can use their knowledge of the entire system to write better programs. Changes in hardware technology and compilers over the past decade have informed this major revision of the 2003 edition.--BOOK JACKET.
Includes bibliographical references (p. 1005-1009) and index.
Keywords: 2 -- 0; 6; Computer systems.;Computers.;Telecommunication.;User interfaces (Computer systems). -- 20; 20; 2